Editorial for the Thematic Issue: Rethinking Innovation Beyond the Fable — Critical Pathways and Alternative Policy Models - Bagattolli, Carolina; de Brito Dias, Rafael (NOvation — Critical Studies of Innovation, 2025)
In recent decades, innovation has achieved an extraordinary position in political, economic and cultural discourse. It has come to be seen as a universal remedy—a panacea capable of addressing social, environmental, economic and political challenges while simultaneously driving growth and competitiveness. As highlighted in the call for this thematic issue and as critically framed by several authors already, this belief rests on a powerful modern narrative: a fable of progress driven by science and technology, a promise that the future will inevitably be better than the present because innovation will carry us there. Yet this fable has obscured the social, political and environmental consequences of innovation systems designed around market logics, competition and technological determinism. It has eclipsed alternative imaginaries of collective flourishing and dismissed deeper questions about who benefits from innovation, who bears its risks, and what other futures might become possible. In response, the field of Critical Studies of Innovation has emerged to interrogate these assumptions. Building on the foundational work of Godin, Vinck, Pfotenhauer and others, scholarship has exposed the ideological character of “innovationism” (Oliveira, 2011) —the belief that innovation is inherently good, that more is always better, and that societal problems are ultimately innovation deficits. The contributions gathered in this issue extend this critique, while also advancing conceptual and empirical foundations for alternative pathways. They address the contradictions of innovation regimes, expose the limits of ‘x-innovation’ (Gaglio et al., 2019) rebrandings, analyse the politics of governance and directionality, and foreground community-based, solidaristic and human-centred approaches that disrupt dominant models. This issue has been deliberately structured to move from historical–epistemic critique, to sectoral and institutional analysis, to territorial experimentation, and finally to conceptual and methodological tools for rethinking innovation. Each article contributes a distinct lens, yet together they build a coherent argument: that the current innovation paradigm—rooted in neoliberalism, technological determinism and a narrow economic rationality—is neither inevitable nor desirable, and that viable, situated alternatives already exist, albeit often marginalised or invisible.